Estudio seroepidemiologico de la tripanosomiasis bovina en el departamento de Cordoba-Colombia - Garcia A., O.=700 1 Vizcaino G., O.; Tenorio, P.
(En, Es)
ilus., 22 ref.
Keywords: GANADO BOVINO; ENFERMEDADES PARASITARIAS; TRIPANOSOMIASIS; MORBOSIDAD; COLOMBIA